Clinical and Biochemical Features in a Case of Familial Hypocalciuric Hypercalcemia Type 3 with AP2S1 Gene Mutation in Codon Arg15His - Mohamed Aashiq; Asma Jassim Malallah; Farheen Khan; Maryam Alsada (Hindawi Limited, 2020)
Familial hypocalciuric hypercalcemia (FHH) is usually a benign condition divided into three types. FHH-3 occurs in about 20% of the cases and is caused due to missense mutations in AP2S1 (adaptor-related protein complex 2 subunit sigma 1) involving the codon Arg15 (p.R15). We report a case of FHH-3 with a heterozygous mutation in the AP2S1 gene on chr19_47349359 C>T, c.44G>A, p.Arg15His. There are a handful of reports describing the clinical features in patients diagnosed with FHH-3. Herein, we describe the laboratory and clinical features associated with a case of FHH-3 with mutation in the Arg15His codon of the AP2S1 gene.